STEROIDAL SAPOGENINS I TRANSFORMATION OF KRYPTOGENIN IN TO DIOSGENIN AND PSEUDO DIOSGENIN - ROSENKRANZ, G; KAUFMANN, ST (LABORATORIOS SYNTEX, CD. MEXICO, DF, MEX, 1948)
1. Kryptogenin and its diacetate have been reduced with Raney nickel to 16-dihydrokryptogenin and its diacetate, respectively. 2. Strong evidence has been presented that the 16-keto group of kryptogenin is more reactive than the 22-keto group. 3. 16-Dihyd
J PHYS SOC JPN
Keywords: STEROIDAL SAPOGENINS. I., TRANSFORMATION, KRYPTOGENIN, DIOSGENIN, PSEUDO DIOSGENIN; QUIMICA; QUIMICA FISICA; QUIMICA AMBIENTAL